In Silico Study: Molecular Docking and Toxicity Prediction of Pyrazoline Derivatives with Potential as Anti-Inflammatory - Minandre Wiratama; Azimatur Rahmi; Muhammad Badrul Huda; Anggi Khairina Hanum Hasibuan (Indonesian Journal of Chemical Studies, 2025)
Research on heterocyclic compounds suggested that pharmacologically active agents featuring pyrazoline played a crucial role in medicinal chemistry. When fused with other heterocycles, pyrazoline, as a quiescent heterocyclic moiety, resulted in the enhancement of biological properties. Therefore, synthesizing these compounds had attracted the attention of researchers focused on designing novel drugs. The addition of substituents to the N-pyrazoline atom and modifications to the benzene ring of pyrazoline compounds were essential for the identification of pyrazoline derivatives exhibiting enhanced biological activity. Extensive research had shown that pyrazoline compounds had significant biological effects, including anti-inflammatory effects. Inflammation was the body's reaction to infection or injury and marked by symptoms such as redness, heat, swelling, and pain. This research involved a computational analysis of pyrazoline compounds utilizing molecular docking with AutoDock Tools and AutoDock Vina software on four pyrazoline derivative compounds (pyrazolines 1-4). Simultaneously, their toxicity was assessed through online pkCSM to evaluate their potential as anti-inflammatory drug candidates. The interaction between the active site of cyclooxygenase-2 (COX-2) receptor (PDB: 4PH9) and pyrazoline derivatives showed that pyrazoline 2 (1-benzoyl-(3-(4-chlorophenyl)-5-(3,4-dimethoxy)-4,5-dihydro-2-pyrazoline) exhibited the highest binding affinity of -8.0 kcal/mol compared to pyrazoline derivatives 1, 3, 4 and ibuprofen as native ligands also in the molecular docking test with values ​​of -7.1; -7.7; -7.6; and -7.1 kcal/mol, respectively. Toxicity evaluation for pyrazoline 2 also suggested that this compound was non-toxic, non-hepatotoxic, and did not induce skin sensitization, with an Oral Rat Acute Toxicity (LOAEL) score of 1.417 log (mg/kg_bw/day).